C-band ring cavity of virtual mirror BEFL with additional pump power - Abd. Rahman, Zubaidah; Mohamad, H.; Md. Yusoff, Nelidya; Mahdi, Mohd Adzir; Hitam, Salasiah; Abas, Ahmad Fauzi (IEEE, 2011)
A Multiwavelength BEFL with virtual mirror concept is demonstrated with an additional pump power to provide higher gain. 616 mW provided by a 975 nm pump is added to the conventional of 130 mW 1480 nm pump. Wide tuning range of 39 nm wavelengths was achieved and maximum of 9 laser lines was observed from the proposed design.